The Effect of Interactive Media on Adolescent Behavior to Prevent Risky Sexual in Manado City - Simak, Valen Fridolin; Renteng, Septriani; Kristamuliana, Kristamuliana (Fakultas Kedokteran, 2022)
Adaptation to adolescent growth and development needs to be optimized, this is because it will harm adolescent health when that age is confused. Various health problems in adolescents include risky sexual (kissing, masturbation, sex). Various previous studies have stated that the misuse of media or technology (smartphones, internet) to access various information including pornographic sites can increase adolescents' engagement in sexual activity because when adolescents continue to be exposed to it, adolescents will feel challenged to do so in real life. Therefore, it is necessary to increase the behavior (Knowledge, Attitude, and Skills) of adolescents through the implementation of interactive media interventions to prevent risky sexual behavior in adolescents. The purpose of this study is to analyze the effect of interactive media on the ability of adolescents through increasing knowledge, attitudes, and skills in preventing risky sexual behavior. The target of the research is teenagers who are in school and are included in the inclusion criteria, including 10-19 years old and unmarried with a large sample of 109 people. The method used in this study is a quasi-experimental without a control group which compares before (pre-test) and after (post-test) the intervention. Each intervention session has different media including lectures, videos, card games, and role plays. Each session will be conducted 1-2x every week with a total of 8 intervention sessions. The results of this study indicate that there is a significant effect between the implementation of interactive media and the knowledge, attitudes, and skills of adolescents to prevent risky sexual intercourse with p-values of 0.002,; 0.001; 0.014. This study concludes that it is hoped that it can improve the ability of adolescents and can be used as a pilot project that continues to be developed into nursing interventions in community settings so that adolescents can avoid deviant behavior, especially risky sexual behavior.